Near Infrared Spectroscopy as a Diagnostic Tool for Screening of Intracranial Hematomas; A Systematic Review and Meta-Analysis - Zarei, Hamed; Zarrin, Amirali; Janmohamadi, Mahrokh; Saadatipour, Narges; Yarahmadi, Mobina; Moeini, Mohammadmobin; Shams Ardekani, Shireen; Safdarian, Ali; Vazirizadeh-Mahabadi , Mohammadhossein; Babaei, Mohammadhossein; et al. (Archives of Academic Emergency Medicine, 2024)
Introduction: Evidence supports the clinical applicability of near-infrared spectroscopy (NIRS) in intracranial hematoma detection in prehospital settings. This systematic review and meta-analysis aimed to determine the diagnostic yield of NIRS for detecting intracranial hematoma in traumatic brain injury (TBI) patients. Methods: A systematic search was performed in July 2024 in Medline, Embase, Scopus, and Web of Science databases. We included studies that evaluated the diagnostic performance of NIRS in detecting intracranial hematoma in both adult and pediatric patients suspected of TBI in prehospital or emergency settings, using brain computed tomography (CT) scan or magnetic resonance imaging as the gold standard. Results: Eighteen studies enrolling 2979 patients were included. NIRS exhibited an Area Under the Curve (AUC) of 0.91 (95% confidence interval [CI]: 0.88, 0.93), with a sensitivity of 0.86 (95% CI: 0.78, 0.91), and specificity of 0.82 (95% CI: 0.72, 0.89) across all age groups. In children, the results demonstrated an AUC of 0.92 (95% CI: 0.89, 0.94), sensitivity of 0.95 (95% CI: 0.21, 1.00), and specificity of 0.81 (95% CI: 0.65, 0.91). Among adults, the AUC was 0.91 (95% CI: 0.88, 0.93), with sensitivity and specificity of 0.86 (95% CI: 0.78, 0.92) and 0.83 (95% CI: 0.70, 0.91), respectively. Performance improved when NIRS was operated by non-physicians (AUC = 0.94 [95% CI: 0.91, 0.96], sensitivity = 0.90 [95% CI: 0.79, 0.95], specificity = 0.85 [95% CI: 0.71, 0.93]) compared to physicians (AUC = 0.90 [95% CI: 0.87, 0.92], sensitivity = 0.88 [95% CI: 0.77, 0.94], specificity = 0.75 [95% CI: 0.59, 0.76]). Patients’ age group and operator type were identified as potential sources of heterogeneity. Sensitivity analyses confirmed the robustness of the findings, particularly in mild TBI cases and studies implementing a ΔOD > 0.2 as the threshold for a positive NIRS result. Conclusion: NIRS proves to be an effective diagnostic tool for detecting traumatic intracranial hematoma in both pediatric and adult groups, with high sensitivity and specificity. Its utility in prehospital triage, operated by physicians or paramedics, underscores its potential for broader clinical application.